C. B. GARCÍA ESTÉVEZ, J. MARÍA ROVIRA (eds.) - Enric Miralles. Archigraphias, 1983-2000 - Blanco, Arturo (ZARCH, 2021)
Carolina B. García-Estévez, Josep María Rovira (eds.) Enric Miralles. Archigraphias, 1983-2000Madrid: Abada editores, 2020. 448 pp. Encuadernación en rústica. Idioma: español. 25 €ISBN: 978-84-17301-04-0